A comprehensive evaluation method of DC voltage sag in medium–low voltage DC distribution system. (November 2022) - Li, Zhenqiang; He, Huiwen; Wang, Lei; Gao, Le; Zhang, Min; Fan, Rui
Abstract: The development of the DC distribution system (DCDS) has attracted increasing attention, due to its technological superiorities in integrating new energy sources and DC power loads more friendly and effectively. In this paper, a comprehensive evaluation method is proposed for the medium–low​ voltage DCDS to handle the voltage sag assessment problem. Firstly, the topology structure and control strategy of the DCDS are stated, and the pragmatic characteristics of DC voltage sag on the medium-voltage and low-voltage sides based on the dual active bridge (DAB) converter are analyzed. Then, considering the difference in the evaluation indexes of the low-voltage and medium-voltage sides of the DCDS, a comprehensive evaluation system is established. Further, the analytic hierarchy process (AHP) and criteria importance through intercriteria correlation (CRITIC) weighting method are applied to achieve comprehensive weighting, and the TOPSIS model is used to describe the severity of DC voltage sag. Using MATLAB, a 10 kV/ 750 V DCDS with the DAB is built, and comparative assessments are performed. The results show that the proposed method can reasonably evaluate the DC voltage sag of the low-voltage and medium-voltage sides. Compared to the evaluation schemes based on the single index, the proposed method can more effectively reflect the waveform features of the DC voltage sag, and it is very appropriate for the voltage dip evaluation of the medium–low voltage DCDS.